2009
DOI: 10.1038/nature08240
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function of mutated C-CBL tumour suppressor in myeloid neoplasms

Abstract: Acquired uniparental disomy (aUPD) is a common feature of cancer genomes, leading to loss of heterozygosity. aUPD is associated not only with loss-of-function mutations of tumour suppressor genes, but also with gain-of-function mutations of proto-oncogenes. Here we show unique gain-of-function mutations of the C-CBL (also known as CBL) tumour suppressor that are tightly associated with aUPD of the 11q arm in myeloid neoplasms showing myeloproliferative features. The C-CBL proto-oncogene, a cellular homologue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
445
1
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(483 citation statements)
references
References 34 publications
20
445
1
14
Order By: Relevance
“…Detailed clinical information of individual samples was given in our previous report. 10 We identified EED mutations in six cases ( Figure 1a and Supplementary Table 1), which were confirmed by repeated amplification and sequencing. None of these mutations are reported in the 1000 genomes database (a deep catalog of human genetic variation) 11 and the Ensemble gene and the transcript sequences currently available.…”
mentioning
confidence: 55%
“…Detailed clinical information of individual samples was given in our previous report. 10 We identified EED mutations in six cases ( Figure 1a and Supplementary Table 1), which were confirmed by repeated amplification and sequencing. None of these mutations are reported in the 1000 genomes database (a deep catalog of human genetic variation) 11 and the Ensemble gene and the transcript sequences currently available.…”
mentioning
confidence: 55%
“…22 CBL is an E3-ubiquitin ligase that marks mutant kinases for degradation. 23 CBL mutations are rare TET oncogene family member 2 (TET2) maps to chromosome 4q24. TET2 mutations occur across several of the gene's 12 exons.…”
Section: Overview Of Mutations Associated With Bcr-abl1-negative Mpnsmentioning
confidence: 99%
“…A recent report demonstrated that CBL mutants, which have lost E3 ligase activity, acts as an oncogene leading to prolonged tyrosine kinase activation after ligand stimulation. 14 Although the nature of CBLinteracting proteins in distinct cellular compartments is well established, the functional importance of these protein --protein interactions is poorly understood. In this report, we show that the CBL suppresses TGF-b signaling by disrupting the Smad pathway.…”
Section: Discussionmentioning
confidence: 99%
“…E3 ligase inactive mutations of CBL, such as Q367P and Y371S, which were discovered in myeloid neoplasm, make normal fibroblast cell lines to form tumor in mouse dorsal subcutaneous spaces. 14 Oncogenic mutants of CBL have been investigated on how they induce carcinogenesis. One of the carcinogenic mechanisms of CBL mutants is the inability to ubiquitinate and degrade cell-growthrelated RTKs due to inactivated E3 ligase functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation